Seconeolitsine, the Novel Inhibitor of DNA Topoisomerase I, Protects against Invasive Pneumococcal Disease Caused by Fluoroquinolone-Resistant Strains - Jose Manuel Tirado-Vélez; David Carreño; David Sevillano; Luis Alou; José Yuste; Adela G. de la Campa (MDPI AG, 2021)
Antibiotic resistance in Streptococcus pneumoniae has increased worldwide, making fluoroquinolones an alternative therapeutic option. Fluoroquinolones inhibit the type II DNA topoisomerases (topoisomerase IV and gyrase). In this study we have evaluated the in vivo activity of seconeolitsine, an inhibitor of topoisomerase I. Levofloxacin (12.5 to 50 mg/kg) or seconeolitsine (5 to 40 mg/kg) were administered every 12 h during two days in mice infected with a serotype 8-resistant strain. At 48 h, a 70% protection was obtained with seconeolitsine (40 mg/kg; p < 0.001). However, survival with levofloxacin was 20%, regardless of the dose. In addition, seconeolitsine decreased bacteremia efficiently. Levofloxacin had higher levels in serum than seconeolitsine (Cmax of 14.7 vs. 1.6; p < 0.01) and higher values of area under the serum concentration-time curve (AUC0-12h of 17.3 vs. 5; p < 0.01). However, seconeolitsine showed higher levels of time to peak concentration and elimination half-life. This is consistent with the higher binding of seconeolitsine to plasma proteins (40% and 80% when used at 1 µg/mL and 50 µg/mL, respectively) in comparison to levofloxacin (12% at 5 µg/mL and 33% at 50 µg/mL). Our results suggest that seconeolitsine would be a promising therapeutic alternative against pneumococcal isolates with high fluoroquinolone resistance levels.